A Comparison of Donor-acceptor Interactions in Borane Complexes of Divalent Tetrylenes(II) and Divalent Tetrylones(0) using Energy Decomposition Analysis Method with Natural Orbital for Chemical Valence Theory. Issue 1 (2nd January 2016) - Nguyen, Thi Ai Nhung; Huynh, Thi Phuong Loan; Le, Thi Hoa; Pham, Van Tat; Dang, Tan Hiep
Abstract: A scheme for chemical bond analysis by combining the energy decomposition analysis (EDA) method with natural orbitals for chemical valence (NOCV) theory has been investigated. Quantum chemical calculations at the BP86/TZ2P+ level of theory are performed for a comparison of chemical bond analysis between tetrylones [BH3 -E(PH3 )2 ] (B3-EP2 ) and tetrylenes [(BH3 -NHEMe ] (B3-NHE ) (E = C to Pb). The EDA-NOCV results suggest that the B–E bond dissociation energies (BDEs) in tetrylones and tetrylenes decrease from the slighter to the heavier homologs. The decrease in the bond strengths from the lighter to the heavier homologs ofB3-EP2 comes mainly from the decrease in the electrostatic attractions ΔEelstat and the orbital interactions ΔEorb, while the decrease in the bond strength from carbeneB3-NHC to plumbyleneB3-NHPb strongly correlates with the decrease in electrostatic term ΔEelstat .